T cell homeostatic proliferation elicits effective antitumor autoimmunity - Wolfgang Dummer; Andreas G. Niethammer; Roberto Baccala; Brian R. Lawson; Norbert Wagner; Ralph A. Reisfeld; Argyrios N. Theofilopoulos (The Journal of Clinical Investigation, 2002)
Development of tumor immunotherapies focuses on inducing autoimmune responses against tumor-associated self-antigens primarily encoded by normal, unmutated genes. We hypothesized that such responses could be elicited by T cell homeostatic proliferation in the periphery, involving expansion of T cells recognizing self-MHC/peptide ligands. Herein, we demonstrate that sublethally irradiated lymphopenic mice transfused with autologous or syngeneic T cells showed tumor growth inhibition when challenged with melanoma or colon carcinoma cells. Importantly, the antitumor response depended on homeostatic expansion of a polyclonal T cell population within lymph nodes. This response was effective even for established tumors, was characterized by CD8+ T cell–mediated tumor-specific cytotoxicity and IFN-γ production, and was associated with long-term memory. The results indicate that concomitant induction of the physiologic processes of homeostatic T cell proliferation and tumor antigen presentation in lymph nodes triggers a beneficial antitumor autoimmune response.